Twinkle's town & country knits : 30 designs for sumptuous living - Chia, Wenlan (New York : Potter Craft, 2008)
Provides patterns and instructions for thirty knitted sweaters and accessories which add twists to classic silhouettes.
Includes index.
Library Journal.
Library Journal, August 2008.
Adult
Keywords: Knitting; Knitting -- Patterns; Knitting; Knitting -- Patterns